2024
DOI: 10.1037/cdp0000524
|View full text |Cite
|
Sign up to set email alerts
|

Late life anxiety and depression symptoms, and suicidal behaviors in racial/ethnic minority older adults in community-based organizations and community clinics in the U.S.

Abstract: Objective: Late life anxiety and depression represent a significant source of disability, with racial/ethnic minority older adults in the U.S. showing marked disparities in healthy aging. Community-based organizations (CBOs) and community clinics serve these populations for preventive care, yet few identify their mental health service needs. We examine the association between race/ethnicity and risk of mild-tosevere symptoms of anxiety and depression, and suicidal behaviors in minority older adults. Method: Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 120 publications
(150 reference statements)
0
3
1
Order By: Relevance
“… 9 In the USA, a multisite randomised controlled trial of community-based older adults reported that 28.1% of participants had mild to severe anxiety symptoms and 30.1% had mild to severe depressive symptoms, with differences in prevalence between ethnic groups. 12 The current study found that the prevalence of depression and anxiety in the community elderly population in Shenzhen was 10.4% and 11.3%, respectively, which was higher than the results of the national population-based epidemiological survey on mental disorders conducted by Huang et al , 2 but lower than the results of studies on the mental health of the elderly population in other regions of China. 6 8 21 Regional differences in study populations greatly influence the findings.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“… 9 In the USA, a multisite randomised controlled trial of community-based older adults reported that 28.1% of participants had mild to severe anxiety symptoms and 30.1% had mild to severe depressive symptoms, with differences in prevalence between ethnic groups. 12 The current study found that the prevalence of depression and anxiety in the community elderly population in Shenzhen was 10.4% and 11.3%, respectively, which was higher than the results of the national population-based epidemiological survey on mental disorders conducted by Huang et al , 2 but lower than the results of studies on the mental health of the elderly population in other regions of China. 6 8 21 Regional differences in study populations greatly influence the findings.…”
Section: Discussioncontrasting
confidence: 78%
“…8 Mental disorders in the elderly population are a challenge worldwide, and an increasing number of studies report a high probability of anxiety and depression among this demographic. [9][10][11][12][13][14][15] In Southern Europe, 9 the gender gap in depression prevalence is wider than in Northern Europe, with older men having a 21% lower risk of depression than older women at 38%. This correlation is attributed to psychosocial, socioeconomic and health factors.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the older population also faces a range of risks and challenges. Prior studies have shown that there were high rates of mental health disorders (typically depression and anxiety) in the older population throughout the world [ [ 38 , 39 ]]. In addition, this group is also more likely to experience decreased sleep quality [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the presence of disturbances in the mindset of individuals with SAD will cause dysfunction in social communication skills and lead to major depressive disorder or MDD (Maleki et al, 2020). These symptoms of depression if not handled properly will result in individuals having suicidal thought or even suicidal behavior (Jimenez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%